PENGARUH COUNTERPRESSURE TERHADAP TINGKAT NYERI PERSALINAN PADA IBU INPARTU KALA I FASE AKTIF DI BPS NURIJAH TRAWAS MOJOKERTO - triwibowo, Heri; Frilasari, Heni (JURNAL KEPERAWATAN SEHAT, 2014)
Childbirth is the process where the baby, placenta and amniotic membranes out of the mothers womb. One effort to overcome the pain by using non-pharmacological methods, such as by providing counterpressure massage techniques. This study aims to determine the effect of counterpressure against the pain of labor in pregnant inpartu when an active phase of the BPS Nurijah Istiqomah, Amd.Keb Trawas Mojokerto district. This research uses experimental methods to design Pre One Group Pre Test - Post Test. The number of samples found there were 13 respondents. Consecutive sampling techniques using sampling. The independent variable is the gift of massage techniques counterpressure, while the dependent variable levels of pain when an active phase of labor. Instruments used in data collection are questionnaires and interview sheets verbal pain scale before and after childbirth treated counterpressure. The results of this study indicate there are 53.8% of respondents who experienced severe pain intensity prior to treatment controlled counterpressure. But after receiving treatment counterpressure as much as 53.8% of respondents claimed to experience pain with moderate intensity. The collected data have been analyzed using statistical tests Wilcoxon Sign Rank Test comparative degrees of significance α = 0.05 obtained value of ρ = 0.013. These results indicate H0is rejected, meaning that there is influence of counterpressure against the pain level when an active phase of labor. Counterpresure can provide distraction and relaxation effects as well as an action that can block transmission of pain impulses from the source of pain bersal of the cervix and corpus uteri that can decrease the intensity of labor pain.Keywords: Counterpressure, Labor Pain, Reveal motherIn Ist Active Phase